Perspektif Etika Bisnis Islam Pada Pedagang Pakaian di Pasar Tradisional - Cici Adelia; Nurseri Hasnah Nasution (Social Science and Contemporary Issues Journal, 2024)
The purpose of this study is to find out how the understanding of Islamic business ethics possessed by clothing traders in the Teluk Lubuk Village Traditional Market, Muara Enim Regency, to find out how the objective conditions and ethics of clothing traders in the Teluk Lubuk Village Traditional Market, Muara Enim Regency, and to find out certain aspects of the Islamic business ethics review of clothing traders in the Teluk Lubuk Village Traditional Market, Muara Enim Regency. This type of research is a field research with primary and secondary data sources. Data collection techniques using observation, interviews and documentation, Data analysis techniques in this study are qualitative descriptive by means of data reduction, data presentation, and data conclusion. The results showed that: First, the understanding of clothing traders in Teluk Lubuk Village Traditional Market, Muara Enim Regency regarding Islamic business ethics concluded that traders do not know what Islamic business ethics are. However, they know that in trading there are rules that have been regulated according to Islamic law. Second, the objective and ethical conditions of clothing traders in this market reflect the dynamics of traditional markets in general, where traders are competing to offer their merchandise at various prices and quality. Clothing traders at Teluk Lubuk Village Traditional Market show various ways and situations in conducting their business. Third, the ethics of clothing traders in the Teluk Lubuk Village Traditional Market, Muara Enim Regency are partly in accordance with Islamic business ethics, and most are not in accordance with Islamic business ethics, namely shirking obligatory prayers, not keeping promises, and hiding information about old or damaged goods.